Cerebral Dominance in Multilinguals - PJ, Kumar; NP, Nataraja; MG, Subrahmanyaiah (Journal of All India Institute of Speech and Hearing)
The present study was an attempt to find out the relationship between the familiarity of language and the hemisphere involved in processing it, A dichotic listening task was administered to 10 adult males. All of them had Kannada as mother tongue and were familiar with English and as well as Hindi. The results indicate that the most familiar language seems to be processed in the left hemisphere